Conference of the Association of Inspectors of Education of the Canary Islands: Colloquies on brain and education - Cabrera Delgado, José Manuel (Avances en Supervisión Educativa, 2017)
Review of the "Colloquium on Brain and Education" Training Conference that took place on November 17, 2017 at the Faculty of Political, Social and Communication Sciences of the University of La Laguna, Tenerife.Conference organized by the Association of Education Inspectors of the Canary Islands (AIDEC) in collaboration with the University Institute of Neuroscience at the University of La Laguna. During the training session the latest advances in neuroscience and its application in the educational field were addressed in order to better understand how the brain works and know the neurocognitive processes involved in learning. The first presentation was given by Dr. Manuel de Vega, Professor of Basic Psychology at the University of La Laguna and Director of the University Institute of Neuroscience. The second of the lectures was given by Dr. Iván Padrón, postdoctoral researcher Agustín de Betancourt of the University of La Laguna in the laboratory of non-invasive brain stimulation of the University Institute of Neuroscience. Finally, a round table was held where several education inspectors debated the contributions of neuroscience to current education.
Keywords: neuroscience; inspectors; education; training session